ANALYZING OF YOUTUBE’S ADVERTISING ON CONSUMER BUYING INTEREST (STUDY CASE: STUDENTS OF SAM RATULANGI UNIVERSITY) - Inkiriwang, Novia A.; Tumbuan, Willem J. F. A.; Tumewu, Ferdinand J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Youtube is a way of advertising video content on Youtube or in search results so people can maximize the user reach. Youtube advertising is a way to reach people attention in order to gain benefit, there are several types of advertising that provide by youtube. Also Buying interest arises after an alternative evaluation process and in the evaluation process, a person will make a series of choices regarding the product to be purchased on the basis of brand and interest The aim of this study is To know the effectiveness of youtube’s advertising on consumer buying interest.  To achieve these objectives the researcher got information from 30 informants using a qualitative study which is an in-depth interview and uses purposive sampling. The results showed The advertising on youtube gets much attention for everyone especially the students of Sam Ratulangi University, the advertising its effective for the youtube user or the college students because all the informants 1 to 30 gave a positive response and opinion about youtube and youtube advertising, the advertising may increase the buying interest, some of the informants ended up buying products by seeing the advertising appear on youtube. Keywords: Youtube Advertisings, Consumer Buying Interest